2021
DOI: 10.3389/fpls.2021.648026
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying Recent Adaptive Diversification of the Chrysanthemum-Group on the Basis of an Updated Multilocus Phylogeny of Subtribe Artemisiinae (Asteraceae: Anthemideae)

Abstract: Understanding the roles played by geography and ecology in driving species diversification and in the maintenance of species cohesion is the central objective of evolutionary and ecological studies. The multi-phased orogenesis of Qinghai-Tibetan Plateau (QTP) and global climate changes over late-Miocene has profoundly influenced the environments and evolution of organisms in this region and the vast areas of Asia. In this study, we investigate the lineage diversification of Chrysanthemum-group in subtribe Arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 125 publications
(183 reference statements)
4
43
0
Order By: Relevance
“…It was found that the affinity between Chrysanthemum and Ajania is very close, and the resolving power of CDS and cpDNA markers were not enough. When eight nuclear sequences were used (Shen et al, 2021), Chrysanthemum and Ajania were well separated with only a few exceptions (Figure 2), which agrees with traditional taxonomy mainly based on capitulum morphology. In Chrysanthemum, two Chinese endemic species with white ray flowers, C. rhombifolium and C. vestitum, are sister to C. indicum complex with yellow/white ray flowers (Figure 2).…”
Section: Intrageneric Relationship Of Chrysanthemum and Origin Of CMsupporting
confidence: 78%
See 3 more Smart Citations
“…It was found that the affinity between Chrysanthemum and Ajania is very close, and the resolving power of CDS and cpDNA markers were not enough. When eight nuclear sequences were used (Shen et al, 2021), Chrysanthemum and Ajania were well separated with only a few exceptions (Figure 2), which agrees with traditional taxonomy mainly based on capitulum morphology. In Chrysanthemum, two Chinese endemic species with white ray flowers, C. rhombifolium and C. vestitum, are sister to C. indicum complex with yellow/white ray flowers (Figure 2).…”
Section: Intrageneric Relationship Of Chrysanthemum and Origin Of CMsupporting
confidence: 78%
“…The number after the taxon name represents the ploidy level. This schematic is compiled mainly based on Shen et al, 2021 , as the phylogenetic topology inferred from low-copy nuclear genes and nrITS could be more convincing than those inferred from cp sequences ( Liu et al, 2012 ; Lu et al, 2022a ). It should be noted that it is challenging to distinguish taxa from each other within C. indicum complex and C. zawadskii complex, respectively.…”
Section: Biodiversity and Phylogenetic Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, on the basis of phylogenetic analysis using nuclear-encoded genes, Shen et al. ( 2021 ) revealed that C. pacificum, Chrysanthemum shiwogiku Kitam., 1935 (syn. Ajania shiwogiku (Kitam.)…”
mentioning
confidence: 99%